THE EFFECT OF JOB STRESS AND LEADERSHIP SUPPORT ON IRING MANTEN WEDDING ORGANIZER EMPLOYEES’ PERFORMANCE - Rendi Alvianto; Sonja Andarini (SEAN Institute, 2023)
To develop competent human resources, it is crucial to provide excellent education, suitable training, and enough social facilities. This study aimed to assess the effect of job stress and leadership support on Iring Manten Wedding Organizer employees' performance. This study employed a quantitative form of methodology. The population consisted of 40 Iring Manten Wedding Organizer employees as the research sample. Based on the processed data results, the sig value of the job stress variable (X1) is 0.003 < 0.05. The value is tcount -3,239 < ttable 2.024. Then, H2 is accepted and H0 is rejected. It means that the job stress has a significant effect, but has no effect on employee performance. Then the sig value on the job stress variable (X2) is 0.000 < 0.05. The value is tcount 4.214 > ttable 2.024. Then, H3 is accepted. It means that leadership support has a significant effect on employee performance.